(untitled) - Angelony, Elvio (New York, 2009)
Varying perspectives on important issues and provides readers with balanced and fair coverage of a topic to form their own opinion or to support their research. This reader is designed to address a number of different issues regarding physical anthropology. Each issue question is relevant to the topic and guides readers through the readings.
Keywords: Physical anthropology,Thể chất con người